A study on the spending pattern of consumer on their disposable income: a case study of UiTM Kelantan / Salmawatti Mohd Sharif - Mohd Sharif, Salmawatti (2006)
The main purpose of this project paper is to study “The Spending Pattern of Consumer on Their Disposable Income : A case study of UiTM Kelantan. The spending pattern refers to the consumer behavior. Consumer behavior is simply the individual purchasing consuming decision of consumer. That ‘purchase’ can be the consumption of goods or services. These goods or services can be both publicly produced or privately produced by organization. The spending pattern of the consumer is measured by how much the consumer spend the monthly disposable income on food, clothes and personal care, housing, credit payment, education, medical care, utilities, saving, recreation and entertainment. The methods that the researcher uses to measure the objective of the study can be achieved by using survey method, data collection and also sampling techniques. The method of sampling is convenience. From the data collected, the researcher can answer the hypothesis and the information should aid the decision maker. Ten of the hypothesis use crosstab and chi-square tests. From the findings, the researcher found that most of the respondents spend on food, clothes and personal care, housing, credit payment, education, medical care, utilities, saving, recreation and entertainment depending on their disposable income. It shows that the Malaysians know how to manage or make the budgeting of their disposable income in appropriate ways